Writing feeling improving film with protective film

By setting a specific maximum height of the rounded corrugation curve between the writing-sensing improved film and the protective film to the thickness ratio of the adhesive layer, the floating and peeling problems caused by temperature changes are solved, ensuring the stability of the writing-sensing improved film and quality.

CN119136979APending Publication Date: 2024-12-13LINTEC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280094533.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-31
Filing Date
2022-12-02
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing writing-sensation-improving films are prone to floating and peeling when temperature changes, resulting in a decrease in quality.

Method used

By establishing a specific maximum height of the rounded corrugation curve to the thickness ratio of the adhesive layer (WEM/a) between the writing-sensation improvement film and the protective film, it is ensured to be above 0.01 and below 1.00, thereby suppressing the occurrence of floating and peeling. .

Benefits of technology

It effectively suppresses the floating and peeling caused by temperature changes, maintains the writing sense and improves the quality of the film, and ensures stability during storage, handling and processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136979A_ABST
    Figure CN119136979A_ABST
Patent Text Reader

Abstract

The invention relates to a writing feeling improving film with a protective film. The present invention relates to a writing feeling improving film with a protective film, in which a writing feeling improving film having a writing feeling improving film base material layer and a writing feeling improving layer and a protective film having an adhesive layer and a protective film base material layer are laminated such that the writing feeling improving layer of the writing feeling improving film and the adhesive layer of the protective film are in contact with each other, the ratio (WEM / a) of the maximum height (WEM) of the rounded waviness curve of the writing feeling improving layer to the thickness a ([mu] m) of the adhesive layer is 0.01-1.00. According to the present invention, it is possible to provide a writing feeling improving film with a protective film, which does not float or peel off even when temperature changes occur during storage, transportation, processing, or the like, and which maintains the quality of the writing feeling improving film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a writing feel improving film with a protective film obtained by laminating a protective film on a writing feel improving film used to improve the writing feel of a stylus pen in a touch panel or the like. Background Art

[0002] In recent years, image display devices (touch panels) with a position detection function that serve as both a display device and an input unit are often used in various electronic devices.

[0003] For such a touch panel, it has been studied to attach a film for improving the writing feeling of a stylus pen (hereinafter referred to as a “writing feeling improving film”) to the outermost surface of the touch panel.

[0004] Regarding the writing feel improving film, for example, disclosed are: a writing feel improving film having a writing feel improving layer having a specific friction force (Patent Document 1); an anti-glare hard coating film for a touch panel that specifies the pen tip resistance and the oleic acid contact angle of a stylus pen (Patent Document 2); a transparent film having a specific total light transmittance and a specific maximum height of a rolling waviness curve (Patent Document 3); a tactile film comprising linear protrusions forming a mesh structure (Patent Document 4); a transparent laminated film having a surface shape having a specific maximum height of a rolling waviness curve and an arithmetic mean roughness (Patent Document 5), etc.

[0005] However, these documents do not describe a laminated body in which a protective film is laminated on a writing feel improving film.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent document 1: WO2020 / 122172 (US2022 / 0033600A1)

[0009] Patent Document 2: Japanese Patent Application Publication No. 2014-232276

[0010] Patent Document 3: Japanese Patent Application Publication No. 2014-97649 (US 2015 / 0291828A1)

[0011] Patent Document 4: Japanese Patent Application Publication No. 2015-54417

[0012] Patent Document 5: Japanese Patent Application Publication No. 2016-196113 (US2018 / 0030229A1) Summary of the invention

[0013] Problems to be solved by the invention

[0014] After manufacturing, such a writing feel improving film is stored, transported, processed, etc. Therefore, in order to protect the surface of the writing feel improving film until the writing feel improving film is used in a touch panel, a protective film is sometimes pre-pasted (laminated) on the film surface. In addition, the writing feel improving film with a protective film laminated on the surface (hereinafter referred to as "writing feel improving film with a protective film") is sometimes also exposed to a high temperature state (40 to 60°C) for a long time during storage and transportation, or is processed at a high temperature state (50 to 90°C) during processing.

[0015] However, due to such a temperature change, there is a problem that the quality of the writing feel improving film is degraded due to the film floating (tunneling) and peeling.

[0016] The present invention has been made in view of the above-mentioned actual situation, and an object of the present invention is to provide a writing feel improving film with a protective film in which the occurrence of floating and peeling due to temperature change is suppressed.

[0017] Means used to solve problems

[0018] The inventors of the present invention have conducted in-depth research on a writing feel improving film with a protective film in order to solve the above-mentioned problem. As a result, they found that the problem can be solved by making the ratio (WEM / a) of the maximum height of the rounding waviness curve (WEM) of the writing feel improving layer relative to the thickness a (μm) of the adhesive layer of the protective film have a specific relationship, thereby completing the present invention.

[0019] Therefore, according to the present invention, the writing feel improving film with a protective film as described below [1] to [3] can be provided.

[0020] [1] A writing feel improving film with a protective film, characterized in that the writing feel improving film having a writing feel improving film substrate layer and a writing feel improving layer and a protective film having an adhesive layer and a protective film substrate layer are laminated in such a manner that the writing feel improving layer of the writing feel improving film is in contact with the adhesive layer of the protective film,

[0021] The ratio (WEM / a) of the maximum height of the rounding waviness curve (WEM) of the writing feel improving layer to the thickness a (μm) of the adhesive layer is 0.01 or more and 1.00 or less.

[0022] [2] The writing feel improving film with a protective film according to [1], characterized in that the maximum height (WEM) of the rounding waviness curve of the writing feel improving layer is not less than 0.1 μm and not more than 20 μm.

[0023] [3] The writing feel improving film with a protective film according to [1] or [2], characterized in that the thickness a (μm) of the adhesive layer is 5 μm or more and 50 μm or less.

[0024] [4] The writing feel improving film with a protective film according to [1] or [2], wherein the interlayer peeling force between the writing feel improving film and the protective film is 800 mN / 25 mm or less.

[0025] Effects of the Invention

[0026] According to the writing feel improving film with a protective film of the present invention, the occurrence of floating and peeling due to temperature changes during storage, transportation, processing, etc. can be suppressed, and therefore, the quality of the writing feel improving film can be maintained. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a schematic diagram showing an example of the layer structure of the writing feel improving film with a protective film of the present invention. DETAILED DESCRIPTION

[0028] The writing feel improving film with a protective film of the present invention is characterized in that it is a writing feel improving film with a protective film in which a writing feel improving film having a writing feel improving film substrate layer and a writing feel improving layer and a protective film having an adhesive layer and a protective film substrate layer are laminated in such a manner that the writing feel improving layer of the writing feel improving film is in contact with the adhesive layer of the protective film, and a ratio (WEM / a) of a maximum height of a rounding waviness curve (WEM) of the writing feel improving layer to a thickness a (μm) of the adhesive layer is 0.01 or more and 1.00 or less.

[0029] Hereinafter, the writing feel improving film with a protective film of the present invention will be described in detail.

[0030] 1) Film for improving writing feel

[0031] The writing feel-improving film according to the present embodiment includes a writing feel-improving film base material layer and a writing feel-improving layer.

[0032] (1) Writing feel improvement film substrate layer

[0033] The writing feel improving film base material layer according to this embodiment has a function of supporting the writing feel improving layer.

[0034] As the material of the writing feel improving film substrate layer, a transparent material can be appropriately selected from conventionally known materials for optical substrates and used.

[0035] Examples thereof include polyester films such as polyethylene terephthalate films, polybutylene terephthalate films, and polyethylene naphthalate films; polyolefin films such as polyethylene films and polypropylene films; cellulose diacetate films, cellulose triacetate films, cellulose acetate butyrate films, polyvinyl chloride films, polyvinylidene chloride films, polyvinyl alcohol films, ethylene-vinyl acetate copolymer films, polystyrene films, polycarbonate films, polymethylpentene films, polysulfone films, polyetheretherketone films, polyethersulfone films, polyetherimide films, polyimide films, fluororesin films, polyamide films, acrylic resin films, polyurethane resin films, norbornene-based polymer films, cyclic olefin-based polymer films, cyclic conjugated diene-based polymer films, vinyl alicyclic hydrocarbon polymer films, polyphenylene sulfide films, and liquid crystal polymer films; cellophane; glass; and laminated films thereof.

[0036] Among them, in combination with the writing feel improving layer, from the viewpoint of being able to well maintain the writing feel of the stylus pen, preferred are polyethylene terephthalate films, polycarbonate films, acrylic resin films, norbornene-based polymer films, and particularly preferred are polyethylene terephthalate films, polycarbonate films, polymethyl methacrylate films, and composite substrates thereof.

[0037] The writing feel improving film substrate layer may be subjected to surface treatment such as oxidation or embossing, primer treatment, etc., on the surface where the writing feel improving layer is to be formed, if desired, in order to improve adhesion with the writing feel improving layer provided on the surface.

[0038] Examples of the oxidation method include corona discharge treatment, plasma discharge treatment, chromating treatment (wet method), flame treatment, hot air treatment, and ozone / ultraviolet treatment.

[0039] Examples of the roughening method include a sandblasting method and a solvent treatment method.

[0040] The primer treatment can be performed by a known method such as coating an adhesive resin material on the surface of the writing feel improving film substrate layer.

[0041] These surface treatments and the like may be appropriately selected according to the material of the base material layer and the like.

[0042] From the perspective of appropriately supporting the writing feel improving layer, processability, protection of the touch panel, and durability against writing with a stylus pen, the thickness of the writing feel improving film substrate layer is preferably 30 to 300 μm, more preferably 90 to 250 μm, particularly preferably 120 to 220 μm, and further preferably 150 to 200 μm.

[0043] (2) Writing feel improvement layer

[0044] The writing feel improving layer described in this embodiment has a function of improving the writing feel of the stylus pen.

[0045] Here, "improving the writing feel of the stylus pen" means that when writing on the writing feel improvement layer with the stylus pen, the vibration feeling when writing on paper with a ballpoint pen can be reproduced and the resistance feeling (degree of friction) when writing on paper with a ballpoint pen can be reproduced.

[0046] The writing feel-improving layer can be formed using a composition for forming a writing feel-improving layer.

[0047] The writing feel improving layer-forming composition can be prepared by, for example, mixing a curable component, fine particles, a surface conditioner, and the like.

[0048] (2-1) Curable Component

[0049] The composition for forming a writing feel improving layer according to the present embodiment preferably contains a curable component as a main component.

[0050] The curable component is a component that is cured by active energy rays such as visible light, ultraviolet rays, electron beams, heat, etc. Examples thereof include active energy ray-curable components and thermosetting components.

[0051] Among them, active energy ray-curable components are preferably used from the viewpoints of the hardness of the formed writing feel improving layer, the heat resistance of the writing feel improving film substrate layer, etc. The writing feel improving film provided with a writing feel improving layer formed of such a material is likely to have a desired WEM value and is likely to satisfy the above-mentioned WEM / a value.

[0052] As the active energy ray-curable component, there can be cited multifunctional (meth)acrylate monomers, (meth)acrylate prepolymers, active energy ray-curable polymers, etc. Among them, from the perspective of having a predetermined hardness and being able to improve the writing feel of the stylus pen, multifunctional (meth)acrylate monomers and / or (meth)acrylate prepolymers are preferred, and multifunctional (meth)acrylate monomers are more preferred. The writing feel improving film provided with a writing feel improving layer formed of such a material is likely to have a desired WEM value and is likely to satisfy the above-mentioned WEM / a value.

[0053] The polyfunctional (meth)acrylate monomer and the (meth)acrylate prepolymer may be used alone or in combination.

[0054] It should be noted that, in this specification, (meth)acrylate refers to acrylate and / or methacrylate. The same applies to other similar terms.

[0055] Examples of the multifunctional (meth)acrylate monomer include 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, hydroxypivalate neopentyl glycol di(meth)acrylate, dicyclopentyl di(meth)acrylate, caprolactone-modified dicyclopentenyl di(meth)acrylate, ethylene oxide-modified phosphoric acid di(meth)acrylate, allylated cyclohexyl di(meth)acrylate, isocyanurate di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and polyisocyanurate. Polyfunctional (meth)acrylates include polyfunctional (meth)acrylates such as propionic acid-modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propionic acid-modified dipentaerythritol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, propylene oxide-modified trimethylolpropane tri(meth)acrylate, tri(acryloyloxyethyl)isocyanurate, pentaerythritol tetra(meth)acrylate, propionic acid-modified dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethylene oxide-modified dipentaerythritol hexa(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate.

[0056] These can be used alone or in combination of two or more.

[0057] Examples of the (meth)acrylate prepolymer include polyester acrylate-based, epoxy acrylate-based, urethane acrylate-based, and polyol acrylate-based prepolymers.

[0058] The polyester acrylate prepolymer can be obtained by esterifying the hydroxyl groups of a polyester oligomer having hydroxyl groups at both ends obtained by condensation of a polycarboxylic acid and a polyol with (meth)acrylic acid, or by esterifying the terminal hydroxyl groups of an oligomer obtained by adding an alkylene oxide to a polycarboxylic acid with (meth)acrylic acid.

[0059] The epoxy acrylate prepolymer can be obtained by reacting (meth)acrylic acid with the oxirane ring of a bisphenol epoxy resin or a novolac epoxy resin having a relatively low molecular weight to form an ester.

[0060] The urethane acrylate prepolymer can be obtained by esterifying a polyurethane oligomer obtained by a reaction of a polyether polyol or a polyester polyol with a polyisocyanate with (meth)acrylic acid.

[0061] The polyol acrylate prepolymer can be obtained by esterifying the hydroxyl group of polyether polyol with (meth)acrylic acid.

[0062] These prepolymers may be used alone or in combination of two or more.

[0063] (2-2) Microparticles

[0064] The composition for forming the writing feel improving layer described in this embodiment preferably contains microparticles. By containing microparticles, the surface of the formed writing feel improving layer is appropriately roughened, and the average value, maximum value, minimum value, and standard deviation of the friction force described later are easily adjusted to the desired range. As a result, the obtained writing feel improving film can show a moderate sense of friction and vibration when writing on the writing feel improving layer with a stylus pen, and can well reproduce the writing feel when writing on paper with a ballpoint pen. In addition, the obtained writing feel improving film is easy to have a desired WEM value and is easy to meet the above-mentioned WEM / a value.

[0065] The above-mentioned microparticles refer to particles having an average particle size larger than the silica nanoparticles described later. For example, the average particle size of the microparticles is preferably 1 to 30 μm, more preferably 3 to 24 μm, particularly preferably 6 to 18 μm, further preferably 9 to 16 μm, and further preferably 11 to 14 μm. By using microparticles having an average particle size in the above-mentioned range, it is easy to adjust the average value, maximum value, minimum value, and standard deviation of the friction force described later to the desired range, and give the writing feel improvement layer a moderate sense of friction and vibration, so as to reproduce the writing feel when writing on paper with a ballpoint pen. In addition, it is easy to adjust the WEM to the desired value, especially by combining it with a protective film, so that it is easy to exert an excellent anti-peeling effect. It should be noted that the average particle size of the above-mentioned microparticles is set to the following value: using a laser diffraction scattering particle size distribution measuring device, a dispersion liquid with a concentration of 5% by mass prepared using methyl ethyl ketone as a dispersion medium is used as a sample and a few drops are used to measure the value obtained.

[0066] The microparticles may be inorganic microparticles or organic microparticles, or resin microparticles having both inorganic and organic properties. Among them, from the viewpoint of the hardness of the formed writing feel improving layer and the viewpoint of facilitating the adjustment of the WEM to a desired value, inorganic microparticles or resin microparticles having both inorganic and organic properties are preferred, and resin microparticles having both inorganic and organic properties are particularly preferred.

[0067] Examples of the inorganic fine particles include fine particles made of silica, alumina, titania, zirconium oxide, tin oxide, indium oxide, cadmium oxide, antimony oxide, etc. Among these, silica fine particles are preferred.

[0068] As organic microparticles, melamine resin microparticles, acrylic resin microparticles (e.g., polymethyl methacrylate resin microparticles, etc.), acrylic-styrene copolymer microparticles, polycarbonate microparticles, polyethylene microparticles, polystyrene microparticles, benzoguanamine resin microparticles, etc. can be listed. The resin constituting the resin microparticles may be cross-linked. Among these, acrylic resin microparticles are preferred, and polymethyl methacrylate resin microparticles are more preferred from the viewpoint of optical properties and hardness.

[0069] As the resin fine particles having both inorganic and organic properties, silicone fine particles (for example, Tospearl series manufactured by Momentive Corporation) are suitable.

[0070] In order to further improve dispersibility, it is also preferred that the surface of the microparticles is modified with a surface modifier.

[0071] In addition, the shape of the microparticles can be spherical or non-spherical. In the case of non-spherical, it can be an irregular shape, or a shape with a large aspect ratio such as a needle-like or flaky shape. It should be noted that in this specification, "irregular shape" is not a regular shape such as a spherical or elliptical shape, but an irregular shape with multiple corners or faces. Regarding the resulting writing feel improvement layer, from the viewpoint of easily adjusting the mean value, maximum value, minimum value, and standard deviation of the friction force described later to the desired range and the viewpoint of easily adjusting WEM to the desired value, the shape of the microparticles is preferably spherical, and especially particularly preferably true spherical.

[0072] The fine particles may be used alone or in combination of two or more.

[0073] The content of the microparticles in the composition for forming the writing feel improving layer is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 17 parts by mass, further preferably 1 to 14 parts by mass, further preferably 3 to 12 parts by mass, and preferably 6 to 11 parts by mass, relative to 100 parts by mass of the curable component. By making the content of the microparticles within the above range, it is easy to adjust the average value, maximum value, minimum value, and standard deviation of the friction force of the obtained writing feel improving layer described later to the desired range, and it is easy to adjust the WEM to the desired value. In particular, by combining with a protective film, it is easy to exert an excellent anti-peeling effect.

[0074] (2-3) Surface Conditioner

[0075] The composition for forming a writing feel improving layer according to the present embodiment preferably contains a surface conditioner.

[0076] By containing a surface regulator, the occurrence of streaky defects and unevenness in the formed writing feel improvement layer is suppressed. As a result, the film thickness becomes uniform, the writing feel improvement film presents a more excellent appearance, and is easy to have the desired optical properties (haze value and total light transmittance, etc.). In addition, the surface of the writing feel improvement layer of the writing feel improvement film is easy to present a good surface state, so it is easy to adjust the average value, maximum value, minimum value, and standard deviation of the friction force described later to the desired range, which can make the writing feel of the writing feel improvement layer better. In addition, it is easy to adjust the WEM to the desired value, especially by combining it with a protective film, so that it is easy to exert an excellent anti-warping effect.

[0077] Examples of the surface conditioner include silicone-based surface conditioners consisting of silicone-based polymers, fluorine-based surface conditioners consisting of fluorine-based polymers, acrylic-based surface conditioners consisting of acrylic-based polymers, and vinyl-based surface conditioners consisting of vinyl-based polymers.

[0078] Here, silicone polymer refers to a polymer mainly containing polysiloxane chains, and fluorine polymer refers to a polymer having a fluorine-substituted monomer as a main monomer unit. In addition, acrylic polymer refers to a polymer having an acrylic ester as a main monomer unit. And, vinyl polymer refers to a polymer containing a monomer having a vinyl group as a main monomer unit.

[0079] The surface conditioner may be used alone or in combination of two or more.

[0080] Among these, silicone-based surface conditioners and fluorine-based surface conditioners are preferred from the viewpoint of surface conditioning performance and compatibility with other components.

[0081] As the silicone-based surface conditioner, a surface conditioner composed of polydimethylsiloxane or modified polydimethylsiloxane is preferred, and a surface conditioner composed of polydimethylsiloxane is more preferred.

[0082] As the fluorine-based surface conditioning agent, a surface conditioning agent containing a compound having a perfluoroalkyl group or a fluorinated alkenyl group in the main chain or the side chain is preferred. As commercially available products, BYK-340 manufactured by BYK Japan, FTERGENT650A manufactured by Neos, Mega facRS-75 manufactured by DIC, Mega facRS-90 manufactured by DIC, V-8FM manufactured by Osaka Organic Chemical Industry Co., Ltd., etc. can be preferably listed, but are not limited to them.

[0083] When the composition for forming the writing feel improvement layer contains a surface conditioner, the content of the surface conditioner in the composition for forming the writing feel improvement layer is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, particularly preferably 0.5 to 3 parts by mass, and further preferably 0.8 to 2 parts by mass relative to 100 parts by mass of the curable component. By making the content of the surface conditioner within the above range, the appearance of the writing feel improvement film can be made better. In addition, it is easy to adjust the average value, maximum value, minimum value, and standard deviation of the friction force described later to the desired range, so that the writing feel of the writing feel improvement layer can be made better.

[0084] (2-4) Other ingredients

[0085] The composition for forming the writing feel improving layer may further contain other components in addition to the above components. Examples of other components include silicon dioxide nanoparticles, photopolymerization initiators, ultraviolet absorbers, antioxidants, light stabilizers, antistatic agents, silane coupling agents, antioxidants, thermal polymerization inhibitors, surfactants, storage stabilizers, plasticizers, lubricants, defoamers, organic fillers, wettability improvers, and coating surface improvers.

[0086] By making the composition for forming the writing feel improving layer contain silica nanoparticles, the hardness and scratch resistance of the formed writing feel improving layer can be effectively improved, and further, the anti-peeling property can be easily contributed. In addition, the optical properties (haze value and total light transmittance, etc.) of the writing feel improving film can be improved, and the occurrence of roughness when using the writing feel improving film can be effectively suppressed.

[0087] The average particle size of the silica nanoparticles is preferably 1 to 300 nm, more preferably 5 to 100 nm, and particularly preferably 10 to 50 nm. The average particle size of the silica nanoparticles can be measured using a laser diffraction scattering particle size distribution measuring device.

[0088] The silica nanoparticles may be in the form of an organosol (colloidal). The organosol form improves the dispersibility of the silica nanoparticles and improves the homogeneity and light transmittance of the formed writing feel improving layer.

[0089] When the composition for forming a writing feel improving layer contains silica nanoparticles, the content of the silica nanoparticles in the composition for forming a writing feel improving layer is preferably 5 to 50 parts by mass, more preferably 10 to 35 parts by mass, and particularly preferably 15 to 25 parts by mass based on 100 parts by mass of the curable component.

[0090] By setting the blending ratio of the silica nanoparticles to the above range, the homogeneity and light transmittance of the formed writing feel improving layer can be maintained more satisfactorily.

[0091] When the composition for forming a writing feel improving layer contains an active energy ray-curable component as a curable component, it is preferable to further contain a photopolymerization initiator. By containing a photopolymerization initiator, the curing reaction by irradiation with active energy rays can be more easily performed.

[0092] Examples of the photopolymerization initiator used include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin isobutyl ether, acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-propane-1 -ketone, 4-(2-hydroxyethoxy)phenyl-2(hydroxy-2-propyl)ketone, benzophenone, p-phenylbenzophenone, 4,4'-diethylaminobenzophenone, dichlorobenzophenone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-aminoanthraquinone, 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, benzyl dimethyl ketal, acetophenone dimethyl ketal, p-dimethylaminobenzoate, etc. These may be used alone or in combination of two or more.

[0093] When the composition for forming a writing feel improving layer contains a photopolymerization initiator, the content of the photopolymerization initiator in the composition for forming a writing feel improving layer is preferably 1 to 20 parts by mass, more preferably 2 to 10 parts by mass, based on 100 parts by mass of the curable component, from the viewpoint of the effect of adding the photopolymerization initiator.

[0094] The writing feel improving layer-forming composition may contain a solvent for the purpose of improving coating properties, adjusting viscosity, adjusting solid content concentration, and the like.

[0095] The solvent used is not particularly limited as long as the curing components and the like are dissolved and the microparticles and the like are dispersed. Specific examples of the solvent include alcohols such as methanol, ethanol, isopropanol, butanol, and octanol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; esters such as ethyl acetate, butyl acetate, ethyl lactate, and γ-butyrolactone; ethers such as ethylene glycol monomethyl ether (methyl cellosolve), ethylene glycol monoethyl ether (ethyl cellosolve), diethylene glycol monobutyl ether (butyl cellosolve), and propylene glycol monomethyl ether; aromatic hydrocarbons such as benzene, toluene, and xylene; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; and the like.

[0096] These solvents can be used alone or in combination of two or more.

[0097] The content of the solvent is usually 10 to 300 parts by mass, preferably 30 to 200 parts by mass, based on 100 parts by mass of the curable component.

[0098] (3) Method for forming writing feel improving layer

[0099] The writing feel-improving layer can be formed by applying the writing feel-improving layer-forming composition on the writing feel-improving film base layer to a desired film thickness, and drying and curing the resulting coating.

[0100] As a method for applying the composition for forming a writing feel improving layer, a conventionally known coating method such as a bar coating method, a knife coating method, a roll coating method, a plate coating method, a die coating method, a gravure coating method, etc. can be used.

[0101] The drying temperature of the coating film of the obtained writing feel improving layer-forming composition is usually 40 to 120° C., and the drying time is usually about 30 seconds to 5 minutes.

[0102] When the curable component in the writing feel improving layer-forming composition is active energy ray-curable, the coating film of the writing feel improving layer-forming composition can be cured by irradiating the coating film with active energy rays such as ultraviolet rays and electron beams.

[0103] Ultraviolet irradiation can be performed using a high pressure mercury lamp, an H lamp manufactured by Heraeus, a xenon lamp, or the like. The amount of ultraviolet irradiation is preferably an illuminance of 50 to 1000 mW / cm 2 , Light intensity 50~1000mJ / cm 2 , more preferably 100 to 500 mW / cm 2 , Light intensity 100~500mJ / cm 2 .

[0104] The electron beam irradiation can be performed using an electron beam accelerator or the like, and the irradiation amount of the electron beam is preferably about 10 to 1000 krad.

[0105] When the curable component in the writing feel improving layer-forming composition has thermosetting properties, the coating film of the writing feel improving layer-forming composition can be cured by heating the coating film at a predetermined temperature for a predetermined time.

[0106] The thickness of the writing feel improving layer formed is not particularly limited, but is preferably 0.8 to 30 μm, more preferably 1 to 20 μm, particularly preferably 2 to 15 μm, preferably 3 to 12 μm, more preferably 4 to 10 μm, and most preferably 5 to 8 μm. By making the thickness of the writing feel improving layer within the above range, the writing feel when writing on paper with a ballpoint pen can be reproduced more well. In addition, it is easy to adjust the WEM to a desired value, especially by combining it with a protective film, so that an excellent anti-warping effect can be easily exerted.

[0107] A moderate concavo-convex structure is formed on the surface of the writing feel improving layer of the present invention. The maximum height (WEM) of the rounding waviness curve of the writing feel improving film (writing feel improving layer) is preferably 0.1 μm or more, preferably 0.5 μm or more, particularly preferably 1.0 μm or more, and further preferably 2.0 μm or more. In addition, the maximum height (WEM) of the rounding waviness curve of the writing feel improving layer is preferably 20 μm or less, more preferably 16.0 μm or less, particularly preferably 12.0 μm or less, further preferably 8.0 μm or less, preferably 5.0 μm or less, and most preferably 3.0 μm or less.

[0108] If WEM is in this range, when input is performed using a stylus pen in the touch panel, it can be inferred that the pen tip appropriately scratches the convex portion, and the writing feel can be adjusted approximately constantly at the beginning and during the writing of the pen input. In addition, it is easy to adjust the average value, maximum value, minimum value, and standard deviation of the friction force described later to the desired range, so that the writing feel of the writing feel improvement layer can be made better. Furthermore, when the writing feel improvement layer having a surface shape showing the WEM in the above range is adhered to the writing feel improvement layer using the adhesive layer of the protective film, the thickness of the adhesive layer and the surface shape of the writing feel improvement layer having appropriate concave and convex will exert appropriate adhesion. Thus, even if temperature changes are applied during storage, transportation, processing, etc., peeling can be suppressed.

[0109] In addition, as described later, it is necessary to design the film so that the ratio (WEM / a) of the WEM to the thickness a (μm) of the adhesive layer of the protective film is greater than 0.01 and less than 1.00, preferably greater than 0.01 and less than 1.00, more preferably greater than 0.03 and less than 0.80, particularly preferably greater than 0.06 and less than 0.70, and further preferably greater than 0.07 and less than 0.60.

[0110] The maximum height (WEM) of the spherical waviness curve of the writing feel improving layer can be measured in accordance with JIS B0610: 2001. Specifically, it can be measured by the method described in the examples described below.

[0111] The arithmetic mean roughness (Ra) of the writing feel improving film (writing feel improving layer) is preferably 0.1 to 1 μm, more preferably 0.2 to 0.9 μm, particularly preferably 0.3 to 0.8 μm, and further preferably 0.4 to 0.7 μm.

[0112] The ten-point average roughness (RzJIS) of the writing feel improving film (writing feel improving layer) is preferably 1 to 15 μm, more preferably 3 to 10 μm, and particularly preferably 5 to 8 μm.

[0113] Since the arithmetic mean roughness (Ra) and the ten-point mean roughness (Rz) of the writing feel improving film (writing feel improving layer) are of such values, it is easy to adjust the average value, maximum value, minimum value, and standard deviation of the friction force described later to the desired range, and the writing feel of the writing feel improving layer can be made better. Furthermore, in complement to the above-mentioned WEM, the writing feel improving layer presents a surface shape with moderate concavities and convexities, and when the adhesive layer of the protective film is attached to the writing feel improving layer, the adhesive layer and the writing feel improving layer exhibit moderate adhesion. As a result, even if temperature changes are applied during storage, transportation, processing, etc., the occurrence of peeling can be suppressed.

[0114] The arithmetic mean roughness (Ra) and the ten-point average roughness (RzJIS) can be measured using a surface roughness measuring device in accordance with JIS B0601:2013.

[0115] The average value of the frictional force between the writing feel improving film (writing feel improving layer) and the stylus pen during writing is preferably 100 to 1200 mN, more preferably 200 to 800 mN, particularly preferably 250 to 500 mN or more, and further preferably 300 to 400 mN.

[0116] The maximum value of the frictional force between the writing feel improving film (writing feel improving layer) and a stylus pen during writing is preferably 200 to 1500 mN, particularly preferably 250 to 1000 mN, and further preferably 300 to 600 mN.

[0117] The minimum value of the frictional force between the writing feel improving film (writing feel improving layer) and the stylus pen during writing is preferably 80 to 1200 mN, more preferably 120 to 1000 mN, particularly preferably 200 to 700 mN, and further preferably 240 to 500 mN.

[0118] The standard deviation of the frictional force between the writing feel improving film (writing feel improving layer) and a stylus pen during writing is preferably 10 to 60 mN, more preferably 12 to 45 mN, particularly preferably 14 to 30 mN, and further preferably 16 to 20 mN.

[0119] By making any or all of the average value, maximum value, minimum value, and standard deviation of the friction force within the above range, the vibration sense transmitted to the hand holding the stylus pen can easily and well reproduce the vibration sense obtained when writing on paper with a ballpoint pen. It should be noted that the physical properties related to the friction force can be measured by the method described in the examples described later.

[0120] The writing feel improving layer of the writing feel improving film of the present invention has excellent scratch resistance. In the evaluation of scratch resistance using steel wool, preferably no appearance change is observed. Specifically, the surface of the writing feel improving layer is scratched at 250 g / cm2 using #0000 steel wool in accordance with JIS K5600-5-10. 2 After rubbing for 10 cm and 10 back and forth times with a load of 10000, the surface has preferably 3 or less scratches, and more preferably no damage. Thus, when used on the surface of a display such as a touch panel, the surface protective property can be excellent, and the aesthetics of the touch panel can be well maintained.

[0121] The scratch resistance can be evaluated by the method described in the test examples described later.

[0122] The pencil hardness of the writing feel improvement film (writing feel improvement layer) of the present invention is preferably H or more, preferably 2H or more, particularly preferably 3H or more, and further preferably 4H or more. In addition, the pencil hardness is usually 9H or less, preferably 7H or less, and more preferably 5H or less. By having this hardness, it has excellent scratch resistance, and when used on the surface of a display body such as a touch panel, it exerts excellent surface protection. In particular, the surface is not easily damaged, so the beauty of the touch panel can be well maintained.

[0123] The pencil hardness can be measured according to JIS K5600 using a pencil scratch hardness tester.

[0124] The total light transmittance (%) of the writing feel improving film of the present invention is preferably 80 (%) or more, more preferably 85% or more, and further preferably 90% or more. Thus, the writing feel improving film has excellent transparency and can also exhibit good image recognition when applied to a touch panel. The upper limit of the total light transmittance is usually 100%.

[0125] The total light transmittance can be measured using a haze meter in accordance with JIS K 7361-1, after correction using a blank, by irradiating light from the writing feel improving layer side.

[0126] The haze of the writing feel improving film (writing feel improving layer) of the present invention is preferably 0 to 50%, more preferably 1 to 40%, particularly preferably 5 to 30, and further preferably 10 to 22%. Thus, the writing feel improving film has excellent transparency and can also exhibit good image recognition when applied to a touch panel.

[0127] The haze can be measured using a haze meter in accordance with JIS K 7136:2000.

[0128] 2) Protective film

[0129] The writing feel improving film with a protective film of the present invention uses a protective film having a protective film substrate layer and an adhesive layer. The protective film has the function of preventing the surface of the writing feel improving film from being damaged and dirt from being attached.

[0130] (1) Protective film substrate layer

[0131] The material of the protective film substrate layer according to the present embodiment is not particularly limited, and examples thereof include conventionally known materials used as protective film substrate layers of optical films. Specifically, examples thereof include the same materials as exemplified as the above-mentioned writing feel improving film substrate layer.

[0132] Among them, from the viewpoint of handleability, ease of acquisition, and easier achievement of the effects of the present invention, preferred are polyethylene terephthalate films, polybutylene terephthalate films, polyethylene naphthalate films, polycarbonate films, polypropylene films, polyimide films, polyetherimide films, polymethylpentene films, polyphenylene sulfide films, and liquid crystal polymer films, and more preferred are polyethylene terephthalate films, polypropylene films, and polycarbonate films.

[0133] The protective film base material layer may be a single layer formed of one of these films, or may be a layer in which two or more of these films are laminated.

[0134] The protective film substrate layer can be subjected to surface treatment such as oxidation and convexification and primer treatment in the same manner as described in the above-mentioned writing feel improving film substrate layer. These surface treatment methods are appropriately selected depending on the type of the protective film substrate layer.

[0135] The thickness of the protective film substrate layer can be appropriately set from the viewpoints of operability, cost, etc. The thickness of the protective film substrate layer is preferably 10 to 300 μm, more preferably 20 to 200 μm, particularly preferably 25 to 150 μm or more, further preferably 30 to 120 μm, and more preferably 35 to 110 μm. As a result, the interlayer peeling force described later is easily within the specified range.

[0136] (2) Adhesive layer

[0137] The adhesive layer can make it easier and more secure to bond the protective film base layer and the writing feel improving film to each other.

[0138] As the adhesive constituting the adhesive layer, an adhesive commonly used in optical film applications can be used. Examples thereof include acrylic adhesives, rubber adhesives, silicone adhesives, urethane adhesives, polyester adhesives, polyvinyl ether adhesives, etc. In addition, the adhesive can be any one of an emulsion type, a solvent type, or a solvent-free type. Furthermore, the adhesive may have a cross-linked structure or may not have a cross-linked structure.

[0139] Among these, from the viewpoint of exhibiting the desired adhesion, optical properties, and excellent durability, an acrylic adhesive containing a (meth)acrylate polymer as a base polymer is preferred, and an acrylic adhesive containing a (meth)acrylate polymer as a base polymer and having a cross-linked structure is more preferred. It should be noted that in this specification, "polymer" also includes the concept of "copolymer".

[0140] The monomer units constituting the (meth)acrylate polymer may be appropriately selected from the viewpoints of transparency, adhesive strength, etc., and are particularly preferably monomers containing an alkyl (meth)acrylate and a monomer having a reactive functional group in the molecule (reactive functional group-containing monomer).

[0141] The (meth)acrylate polymer can exhibit preferred adhesiveness by containing a (meth)acrylate alkyl ester as a monomer unit constituting the polymer. As the (meth)acrylate alkyl ester, one having an alkyl group with 1 to 20 carbon atoms is preferred. The alkyl group may be linear or branched, or may have a cyclic structure.

[0142] As the (meth)acrylic acid alkyl esters having 1 to 20 carbon atoms in the alkyl group, for example, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, adamantyl (meth)acrylate, etc. can be listed. Among them, from the viewpoint of easily adjusting the interlayer peeling force described later to the desired value, methyl (meth)acrylate and 2-ethylhexyl (meth)acrylate can be preferably listed. They can be used alone or in combination of two or more.

[0143] The (meth)acrylate polymer preferably contains 30 to 99.9% by mass of an alkyl (meth)acrylate as a monomer unit constituting the polymer, particularly preferably 50 to 99.5% by mass, and further preferably 70 to 99% by mass, relative to all monomer units. By setting the content within this range, it is easy to adjust the interlayer peeling force described later to a desired value.

[0144] The (meth)acrylate polymer contains a monomer containing a reactive functional group as a monomer unit constituting the polymer, and thus reacts with a crosslinking agent described below via the reactive functional group derived from the monomer containing the reactive functional group, thereby forming a crosslinked structure (three-dimensional network structure) to obtain a pressure-sensitive adhesive having a desired cohesive force.

[0145] As the monomer containing reactive functional groups, preferably there can be listed monomers having hydroxyl groups in the molecule (hydroxyl-containing monomers), monomers having carboxyl groups in the molecule (carboxyl-containing monomers), monomers having amino groups in the molecule (amino-containing monomers), etc. Among them, from the viewpoint of easily adjusting the crosslinking density, easily obtaining the adhesive with the desired cohesive force, and the viewpoint of the interlayer peeling force described later, preferably hydroxyl-containing monomers or carboxyl-containing monomers. These monomers containing reactive functional groups can be used alone or in combination of two or more.

[0146] Examples of hydroxyl-containing monomers include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among the above, hydroxyalkyl (meth)acrylates having a hydroxyalkyl group having 1 to 4 carbon atoms are preferred. These may be used alone or in combination of two or more.

[0147] As the carboxyl group-containing monomer, for example, ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid can be cited. Among them, acrylic acid is preferred from the viewpoint of easily satisfying the interlayer peeling force described later. These can be used alone or in combination of two or more.

[0148] In the (meth)acrylate polymer, as a monomer unit constituting the polymer, it is preferred that 0.1 to 20% by mass of a monomer containing a reactive functional group is contained relative to all monomer units, more preferably 0.5 to 10% by mass, and particularly preferably 0.8 to 3% by mass. Thus, the (meth)acrylate polymer is likely to undergo a desired crosslinking reaction between crosslinking agents, and as a result, the obtained adhesive is likely to have good cohesive force, and the interlayer peeling force described later is likely to be adjusted to a desired value.

[0149] The (meth)acrylate polymer may further contain other monomers as monomers constituting the polymer. As the other monomers, for example, (meth)acrylate containing alicyclic structure such as glycidyl (meth)acrylate, dicyclopentanyl (meth)acrylate, adamantyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxyethyl (meth)acrylate, etc. can be cited; (meth)acrylate alkoxyalkyl esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; non-crosslinked acrylamides such as acrylamide and methacrylamide; non-crosslinked (meth)acrylates with tertiary amino groups such as N,N-dimethylaminoethyl (meth)acrylate and N,N-dimethylaminopropyl (meth)acrylate; vinyl acetate; styrene, etc. Among them, from the viewpoint of the cohesive force of the obtained (meth)acrylate polymer (A) and the viewpoint of the interlayer peeling force described later, glycidyl (meth)acrylate is preferred, and glycidyl methacrylate is particularly preferred. They can be used alone or in combination of two or more.

[0150] The (meth)acrylate polymer preferably contains 0.1 to 10% by mass of other monomers as monomer units constituting the polymer, particularly preferably 0.2 to 5% by mass, and further preferably 0.3 to 1% by mass, relative to all monomer units. This makes it easy for the obtained adhesive to have good cohesive force, and it is easy to adjust the interlayer peeling force described later to a desired value.

[0151] The polymerization method of the (meth)acrylate polymer in the present embodiment is not particularly limited, and it can be a random polymer or a block polymer. In addition, the acrylic polymer can be obtained by polymerizing the above-mentioned monomers using a conventional method. It can be prepared by polymerization, for example, by emulsion polymerization, solution polymerization, suspension polymerization, bulk polymerization, aqueous solution polymerization, etc. Among them, from the viewpoint of stability during polymerization and ease of handling during use, it is preferably prepared by solution polymerization in an organic solvent.

[0152] The weight average molecular weight of the (meth)acrylate polymer is preferably 100,000 to 3,000,000, more preferably 300,000 to 2,000,000, particularly preferably 450,000 to 1,500,000, and further preferably 600,000 to 1,000,000. This makes it easier for the resulting adhesive to have good cohesive force and to adjust the interlayer peeling force described below to a desired value.

[0153] It should be noted that the adhesive composition described in this embodiment may contain one of the above-mentioned (meth)acrylate polymers, or may contain two or more of them. In addition, the adhesive composition described in this embodiment may contain the above-mentioned (meth)acrylate polymer and other (meth)acrylate polymers.

[0154] By including a crosslinking agent, the (meth)acrylate polymer can be crosslinked by heating the adhesive composition to form a good three-dimensional network structure, thereby further improving the cohesive force of the resulting adhesive and making it easier to adjust the interlayer peeling force described below to a desired value.

[0155] Examples of the crosslinking agent are preferably crosslinking agents that react with reactive functional groups possessed by the (meth)acrylate polymer, and examples thereof include isocyanate crosslinking agents, epoxy crosslinking agents, amine crosslinking agents, melamine crosslinking agents, aziridine crosslinking agents, hydrazine crosslinking agents, aldehyde crosslinking agents, oxazoline crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, and ammonium salt crosslinking agents.

[0156] Among the above crosslinking agents, isocyanate crosslinking agents, epoxy crosslinking agents, and aziridine crosslinking agents are preferably used from the viewpoint of being easy to react with the reactive functional groups possessed by the (meth)acrylate polymer and being easy to adjust the interlayer peeling force described later to a desired value. The crosslinking agent can be used alone or in combination of two or more.

[0157] When the adhesive composition contains a crosslinking agent and a (meth)acrylate polymer, the content of the crosslinking agent in the adhesive composition is preferably 0.01 to 5 parts by mass, more preferably 0.1 to 4 parts by mass, particularly preferably 0.5 to 3 parts by mass, and further preferably 1 to 2 parts by mass relative to 100 parts by mass of the (meth)acrylate polymer. As a result, the obtained adhesive is likely to exert a more excellent cohesive force, and it is easy to adjust the interlayer peeling force described later to a desired value.

[0158] In addition, the pressure-sensitive adhesive layer may contain other components depending on the purpose.

[0159] Other components include tackifiers, plasticizers, antistatic agents, ultraviolet absorbers, silane coupling agents, rust inhibitors, antioxidants, light stabilizers, softeners, refractive index adjusters, etc. It should be noted that the polymerization solvent and dilution solvent from the production of the (meth)acrylate polymer are not included in the additives constituting the adhesive composition.

[0160] When the adhesive composition contains a plasticizer, the content of the crosslinking agent in the adhesive composition is preferably 0.1 to 50 parts by mass, more preferably 1 to 35 parts by mass, particularly preferably 4 to 20 parts by mass, and further preferably 8 to 15 parts by mass relative to 100 parts by mass of the (meth)acrylate polymer. As a result, the obtained adhesive is likely to exert a more excellent cohesive force and it is easy to adjust the interlayer peeling force described later to a desired value.

[0161] The storage modulus of the adhesive of the present invention is preferably 0.010 to 1 MPa, more preferably 0.011 to 0.6 MPa, and particularly preferably 0.012 to 0.3 MPa. This allows the adhesive layer and the writing feel improving layer to exhibit appropriate adhesion, and the anti-peeling effect is improved.

[0162] The storage modulus can be measured in accordance with JIS K7244-1.

[0163] The thickness a of the adhesive layer is preferably 3 μm or more, more preferably 5 μm or more, and particularly preferably 10 μm or more. In addition, the thickness of the adhesive layer is usually 300 μm or less. Furthermore, from the perspective of better reproducing the writing feel when writing on paper with a ballpoint pen and thinning the total thickness of the touch panel with a writing feel improvement film, it is preferably 200 μm or less, more preferably 100 μm or less, particularly preferably 50 μm or less, and preferably 30 μm or less.

[0164] As described later, the writing feel improving film needs to be designed so that the ratio (WEM / a) of the WEM of the writing feel improving layer to the thickness a (μm) of the adhesive layer is 0.01 or more and 1.00 or less.

[0165] (3) Protective film

[0166] The method for producing the protective film having an adhesive layer is not particularly limited, and can be formed, for example, by applying the adhesive layer-forming composition on the protective film substrate layer to a desired film thickness by a known coating method and drying the resulting coating.

[0167] The pressure-sensitive adhesive layer-forming composition generally contains a base polymer, a solvent, and a cross-linking agent, and may contain fine particles, a tackifier, a plasticizer, an antistatic agent, an ultraviolet absorber, and the like as desired.

[0168] In addition, the protective film may be produced by forming a pressure-sensitive adhesive layer on the writing feel-improving layer as described above, and overlaying a protective film substrate thereon and pressure-bonding (laminating) the layers.

[0169] 3) Writing feel improvement film with protective film

[0170] The writing feel-improving film with a protective film of the present invention is laminated in such a manner that the writing feel-improving layer of the writing feel-improving film and the adhesive layer of the protective film are in contact with each other.

[0171] The writing feel improving film with a protective film of the present invention may be in the form of a long strip (belt) or a short strip (single sheet).

[0172] The schematic diagram of the layer constitution of the writing feel improving film with a protective film of the present invention is shown in Figure 1 .

[0173] That is, the writing feel improving film with a protective film of the present invention is formed by laminating the writing feel improving film 10 and the protective film 20 such that the writing feel improving layer 2 is in contact with the adhesive layer 3 of the protective film.

[0174] The method for producing the writing feel improving film with a protective film of the present invention is not particularly limited, and can be produced, for example, by overlapping and laminating the aforementioned writing feel improving film and the protective film so that the writing feel improving layer is in contact with the adhesive layer.

[0175] Furthermore, as described above, the writing feel improving film with a protective film of the present invention can be produced by forming an adhesive layer on the writing feel improving layer of the writing feel improving film and laminating a protective film substrate thereon.

[0176] Regarding the writing feel improving film with a protective film of the present invention, the ratio of the maximum height of the rounding waviness curve (WEM) of the writing feel improving layer to the thickness a (μm) of the adhesive layer "WEM / a" is preferably 0.01 or more, more preferably more than 0.01, particularly preferably 0.03 or more, further preferably 0.06 or more, and particularly preferably 0.07 or more. In addition, "WEM / a" is preferably 1.00 or less, more preferably less than 1.00, particularly preferably 0.80 or less, further preferably 0.70 or less, and particularly preferably 0.60 or less.

[0177] The writing feel improving film with a protective film of the present invention is designed so that the value of "WEM / a" falls within this range. Therefore, even if temperature changes occur during storage, transportation, processing, etc., floating and peeling are unlikely to occur between the layers of the protective film and the writing feel improving film, and the quality of the writing feel improving film can be maintained.

[0178] In the writing feel improving film with a protective film of the present invention, in order to make the value of "WEM / a" fall within the above range, it is preferred to use a writing feel improving film in which (i) the thickness a of the adhesive layer of the protective film is adjusted according to the WEM value of the writing feel improving layer or (ii) a writing feel improving film includes a writing feel improving layer having an appropriate WEM according to the thickness a of the adhesive layer of the protective film.

[0179] The fact that floating or peeling does not easily occur between the protective film and the writing feel improving film can be confirmed by, for example, the fact that even when a sample (5 cm×5 cm) of the writing feel improving film with the protective film is placed in an oven maintained at 90° C. and left for 1 hour, the peeling from the end is within 1 cm. The degree of peeling from the end is preferably less than 1 cm, more preferably less than 0.5 cm, particularly preferably less than 0.3 cm, and further preferably less than 0.1 cm.

[0180] In the writing feel-improving film with a protective film of the present invention, the interlayer peeling force between the writing feel-improving film and the protective film is preferably 800 mN / 25 mm or less.

[0181] In the writing feel improving film with a protective film of the present invention, the interlayer peeling force between the surface of the writing feel improving layer of the writing feel improving film and the protective film after being placed in an oven maintained at 90° C. and left for 1 hour is preferably 800 mN / 25 mm or less, more preferably 500 mN / 25 mm or less, particularly preferably 300 mN / 25 mm or less, further preferably 200 mN / 25 mm or less, and particularly preferably 150 mN / 25 mm or less.

[0182] In addition, from the viewpoint of preventing the undesirable situation of floating or peeling off from the writing feel improving film when exposed to temperature changes, the lower limit of the interlayer peeling force is preferably 1 mN / 25 mm or more, more preferably 3 mN / 25 mm or more, particularly preferably 6 mN / 25 mm or more, and further preferably 10 mN / 25 mm or more.

[0183] By having such interlayer peeling force, the occurrence of floating and peeling caused by temperature changes during storage, transportation, processing, etc. can be more effectively suppressed, the quality of the writing feel improving film can be maintained, and the protective film can be easily peeled off from the writing feel improving film during use.

[0184] In the writing feel improving film with a protective film of the present invention, the interlayer peeling force between the surface of the writing feel improving layer of the writing feel improving film and the protective film in a state before applying a heat history accompanied by a temperature change such as 90°C for 1 hour is preferably 800 mN / 25 mm or less, more preferably 500 mN / 25 mm or less, particularly preferably 200 mN / 25 mm or less, further preferably 120 mN / 25 mm or less, and among them, preferably 90 mN / 25 mm or less.

[0185] In addition, from the viewpoint of preventing the undesirable situation of floating or peeling off from the writing feel improving film when exposed to temperature changes, the lower limit of the interlayer peeling force is preferably 5 mN / 25 mm or more, more preferably 8 mN / 25 mm or more, particularly preferably 11 mN / 25 mm or more, and further preferably 14 mN / 25 mm or more.

[0186] By having such interlayer peeling force, the occurrence of floating and peeling caused by temperature changes during storage, transportation, processing, etc. can be more effectively controlled, the quality of the writing feel improving film can be maintained, and the protective film can be easily peeled off from the writing feel improving film during use.

[0187] The interlayer peeling force between the writing feel improving film and the protective film can be measured by the method described in Examples.

[0188] The writing feel improving film with a protective film of the present invention can be used as a writing feel improving film constituting the outermost surface of a touch panel (image display device with a position detection function) to which a stylus pen is applied by peeling off the protective film from the writing feel improving film.

[0189] Specifically, the writing feel improving film is laminated on a cover material in a touch panel having a display module such as a liquid crystal (LCD) module, a light emitting diode (LED) module, an organic electroluminescent (organic EL) module, a touch sensor, etc., so that the cover material is in contact with the writing feel improving film substrate layer. The writing feel improving film can be attached via an adhesive layer.

[0190] The stylus pen using the writing feel improving film is not particularly limited, and examples thereof include a stylus pen having a polyacetal pen tip, a stylus pen having a hard felt pen tip, and a stylus pen having an elastomer pen tip.

[0191] The above-described embodiments are described for easy understanding of the present invention and do not limit the present invention at all. Therefore, the elements disclosed in the above-described embodiments include all design changes and equivalents within the technical scope of the present invention.

[0192] For example, the writing feel-improving film with a protective film of the present invention may be laminated with other layers. Examples of the other layers include an adhesive layer laminated on the writing feel-improving film substrate layer side and a release film.

[0193] It should be noted that, in the present specification, when "X to Y" (X and Y are arbitrary numbers) is written, unless otherwise specified, it includes the meaning of "X or more and Y or less", and also includes the meaning of "preferably greater than X" or "preferably less than Y". In addition, when "X or more" (X is an arbitrary number) is written, unless otherwise specified, it includes the meaning of "preferably greater than X", and when "Y or less" (Y is an arbitrary number) is written, unless otherwise specified, it includes the meaning of "preferably less than Y".

[0194] Example

[0195] Hereinafter, the present invention will be described in more detail with reference to Examples and the like, but the scope of the present invention is not limited to these Examples and the like.

[0196] (Manufacturing Example 1) Preparation of Writing Feel Improved Film A

[0197] An active energy ray-curable component containing a multifunctional urethane acrylate (product name "Opstar Z7530, manufactured by Arakawa Chemical Industries, Ltd.) 100 parts by mass (indicated as a solid content conversion value. The same applies to the components other than the solvent below), 9.0 parts by mass of silicone fine particles (Tospearl 1100, manufactured by Momentive, average particle size: 11.0 μm, true spherical), 1.0 parts by mass of a fluorine-based surface conditioner (Megafac RS-90, manufactured by DIC Corporation), 0.3 parts by mass of a silicone-based surface conditioner (SH28, manufactured by Dow Toray Industries, Ltd., polydimethylsiloxane) and 85.5 parts by mass of 1-methoxy-2-propanol as a solvent were mixed to prepare a composition A for forming a writing feel improving layer.

[0198] The writing feel improving layer-forming composition A was applied to a polyethylene terephthalate (PET) film (Lumirror U403, thickness: 188 μm, manufactured by Toray Industries, Inc.) as a writing feel improving film substrate layer using a Meyer bar to a film thickness of 7 μm to form a coating film, which was then placed in an oven maintained at 70° C. for 1 minute to dry.

[0199] Next, ultraviolet irradiation was performed using an ultraviolet irradiation device (EYE GRANTAGE ECS-401GX, manufactured by EYEGRAPHICS) with a high pressure mercury lamp as a light source under the following irradiation conditions to cure the coating film, thereby producing a writing feel improving film A.

[0200] (UV irradiation conditions)

[0201] Lamp power: 2kW

[0202] Conveying speed: 4.23m / min

[0203] Illuminance: 240mW / cm 2

[0204] Light intensity: 307mJ / cm 2

[0205] The maximum height of the spherical waviness curve (WEM), the arithmetic mean roughness (Ra), and the ten-point average roughness (RzJIS) of the writing feel improving layer of the obtained writing feel improving film A were measured by the methods shown below.

[0206] The writing feel-improving layer of the obtained writing feel-improving film A had a WEM of 2.40 μm, a Ra of 0.66 μm, and a RzJIS of 6.14 μm.

[0207] <Maximum height of rolling waviness curve (WEM)>

[0208] The WEM was measured under the following conditions using a surface roughness profile measuring machine (SV3000S4, manufactured by Mitutoyo Corporation) in accordance with JIS B0610:2001.

[0209] Tip shape of measuring head: spherical

[0210] Measuring head tip radius: 800μm

[0211] Sliding speed: 0.5mm / s

[0212] Measuring length: 16mm

[0213] <Ra,RzJIS>

[0214] The surfaces of the writing feel improving layers of the writing feel improving sheets A, B, and C were measured for arithmetic mean surface roughness Ra (μm) and ten-point average surface roughness RzJIS (μm) using a surface roughness profile measuring machine (SV3000S4, manufactured by Mitutoyo Corporation) in accordance with JIS B0601:2013.

[0215] (Manufacturing Example 2) Preparation of Writing Feel Improved Film B

[0216] A writing feel improving film B was prepared in the same manner as in Production Example 1 except that 1 part by mass of true spherical fine particles composed of cross-linked polymethyl methacrylate (SSX-110, average particle size: 10 μm, manufactured by Sekisui Chemicals Co., Ltd.) was used instead of 9.0 parts by mass of the silicone fine particles.

[0217] The writing feel-improving layer of the obtained writing feel-improving film B had a WEM of 6.28 μm, a Ra of 0.26 μm, and a Rz of 4.03 μm.

[0218] (Manufacturing Example 3) Preparation of Writing Feel Improved Film C

[0219] A writing feel improving film C was prepared in the same manner as in Production Example 1 except that 1 part by mass of true spherical fine particles composed of cross-linked polymethyl methacrylate (SSX-120, average particle size: 20 μm, manufactured by Sekisui Chemicals Co., Ltd.) was used instead of 9.0 parts by mass of the silicone fine particles.

[0220] The writing feel-improving layer of the obtained writing feel-improving film C had a WEM of 15.5 μm, a Ra of 0.34 μm, and a Rz of 8.92 μm.

[0221] 〔Friction force measurement〕

[0222] The friction force between the obtained writing feel improving films A, B, and C and a stylus pen (product name "ACK-2003", pen tip material: felt, pen tip diameter: 0.5 mm, manufactured by Wacom) during writing was measured under the following conditions using a dynamic and static friction measuring machine (Tribomaster TL201Ts, manufactured by Trinity Lab).

[0223] (Measurement conditions)

[0224] Load: 200g

[0225] Test length: 10~100mm

[0226] Speed: 1.6 mm / s (vibration measurement conditions, dynamic friction coefficient measurement conditions)

[0227] Sampling interval: 50ms

[0228] Stylus tip angle: 45°

[0229] The average friction force of the writing feel improving film A was 310 mN, the maximum friction force was 350 mN, the minimum friction force was 240 mN, and the standard deviation of the friction force was 17 mN. The average friction force of the writing feel improving film B was 220 mN, the maximum friction force was 280 mN, the minimum friction force was 220 mN, and the standard deviation of the friction force was 17 mN. The average friction force of the writing feel improving film C was 190 mN, the maximum friction force was 240 mN, the minimum friction force was 210 mN, and the standard deviation of the friction force was 22 mN.

[0230] 〔Pencil hardness〕

[0231] The pencil hardness of the writing feel improving layer-side surface of the obtained writing feel improving films A, B, and C was measured using a pencil scratch hardness tester (product name "No. 553-M", manufactured by Yasuda Seiki Seisaku-sho Co., Ltd.) in accordance with JIS K5600.

[0232] The pencil hardness of the writing feel improving film A was 4H, and the pencil hardness of the writing feel improving films B and C was 3H.

[0233] 〔Scratch resistance〕

[0234] The writing feel improving layer side surfaces of the writing feel improving films A, B, and C were coated with #0000 steel wool at a temperature of 250 g / cm 2 The writing feel improving layer was rubbed back and forth 10 times with a load of 100 and a sliding distance of 10 cm. Thereafter, the writing feel improving layer was visually checked for scratches under a three-wavelength fluorescent lamp and evaluated according to the following criteria.

[0235] ○: No change was observed in the appearance of the writing feel improving layer (the number of observed scratches was 0)

[0236] △: A slight change was observed in the appearance of the writing feel improving layer (the number of observed scratches was 1 or more and less than 3)

[0237] ×: A significant change was observed in the appearance of the writing feel improving layer (the number of scratches observed was 4 or more)

[0238] As a result, the writing feel improving films A and B were 0, and the writing feel improving film C was △.

[0239] (Production Example 4) Preparation of Adhesive Layer-Forming Composition D

[0240] 70 parts by mass of 2-ethylhexyl acrylate, 28.6 parts by mass of methyl acrylate, 0.3 parts by mass of glycidyl methacrylate and 1.1 parts by mass of acrylic acid were copolymerized to prepare a (meth)acrylate polymer. The molecular weight of the obtained (meth)acrylate polymer was measured by the method shown below, and the weight average molecular weight (Mw) was 800,000.

[0241] The weight average molecular weight (Mw) is a polystyrene-equivalent weight average molecular weight obtained by measuring using gel permeation chromatography (GPC) under the following conditions (GPC measurement).

[0242] (Measurement conditions)

[0243] ·GPC measuring device: HLC-8020, manufactured by Tosoh Corporation

[0244] ·GPC column (passed in the following order): manufactured by Tosoh Corporation

[0245] TSK guard column HXL-H

[0246] TSK gel GMHXL (×2)

[0247] TSK gel G2000HXL

[0248] ·Test solvent: tetrahydrofuran

[0249] ·Measurement temperature: 40℃

[0250] Composition D for forming an adhesive layer is prepared by mixing 100 parts by mass of the (meth)acrylate polymer obtained as described above (representing the solid content conversion value. The same applies to the other components except the solvent below), 10.0 parts by mass of dibutoxyethoxyethyl adipate as a plasticizer, 0.9 parts by mass of an aziridine-based crosslinking agent (BXX-5134, manufactured by Toyo Chemical Co., Ltd.) as a crosslinking agent, and 87 parts by mass of toluene as a solvent.

[0251] (Production Example 5) Preparation of Adhesive Layer-Forming Composition E

[0252] In Production Example 4, except that 1.9 parts by mass of a cross-linking agent was used instead of 0.9 parts by mass, the same procedure as in Production Example 4 was carried out to prepare a pressure-sensitive adhesive layer-forming composition E.

[0253] (Production Example 6) Preparation of Adhesive Layer-Forming Composition F

[0254] In Production Example 4, except that 2.8 parts by mass of the cross-linking agent was used instead of 0.9 parts by mass, the same procedure as in Production Example 4 was carried out to prepare a pressure-sensitive adhesive layer-forming composition F.

[0255] (Example 1)

[0256] The adhesive layer-forming composition D obtained in Production Example 4 was applied to a polyethylene terephthalate (PET) film (Lumirror, thickness: 38 μm, manufactured by Toray Industries, Inc.) as a protective film substrate layer using an applicator to a film thickness of 10 μm to form an adhesive layer coating film. Thereafter, the film was placed in an oven maintained at 100° C. for 1 minute to dry, thereby obtaining a protective film including a protective film substrate layer and an adhesive layer.

[0257] Next, the pressure-sensitive adhesive layer of the obtained protective film was laminated to the surface of the writing feel-improving layer of the writing feel-improving film A obtained in Production Example 1 in such a manner that the film came into contact with each other, thereby producing a writing feel-improving film with a protective film.

[0258] (Examples 2 to 15, Comparative Examples 1 to 3)

[0259] In Example 1, except that the type of the writing feel improving film used, the type of the adhesive layer-forming composition, and the thickness of the adhesive layer were set as shown in Table 1 below, the same operation as in Example 1 was carried out to produce writing feel improving films with protective films of Examples 2 to 15 and Comparative Examples 1 to 3.

[0260] Table 1 shows the ratio of the maximum height (WEM) of the spherical waviness curve of the adhesive layer of the writing feel improving films with protective films obtained in Examples 1 to 15 and Comparative Examples 1 to 3 to the thickness a.

[0261] The writing feel improving films with protective films obtained in Examples 1 to 15 and Comparative Examples 1 to 3 were subjected to a peeling test by the method described below.

[0262] The results are shown in Table 1.

[0263] <Peel test>

[0264] The obtained writing feel improving film with a protective film was cut into 5 cm squares to prepare samples. The samples were placed in an oven maintained at 90° C. with the protective film side facing downward. After being placed in the oven for 1 hour, the peeling (cm) between the writing feel improving layer and the protective film was measured and evaluated according to the following criteria.

[0265] It should be noted that the temperature before the test was 23°C.

[0266] 5: Not stripped

[0267] 4: Peeling less than 0.5 cm from the end was observed

[0268] 3: Peeling is observed from the edge to a distance of 0.5 cm or more and less than 1.0 cm

[0269] 2: Peeling is observed from the edge by 1.0 cm or more and less than 1.5 cm

[0270] 1: Peeling of 1.5 cm or more from the edge was observed

[0271] In addition, the interlayer peeling force (adhesive force) between the protective film and the writing feel improving film before and after the peeling test, and the writing feel of the writing feel improving film after the peeling test were measured by the method shown below.

[0272] The results are shown in Table 1.

[0273] <Interlayer Peeling Strength>

[0274] The obtained writing feel improving film with a protective film was cut into 25 mm wide and 110 mm long test pieces to prepare the test pieces. The interlayer peeling force (N / 25 mm) when the protective film was peeled off from the writing feel improving film was measured using a tensile testing machine (manufactured by TENSILON, ORIENTEC) in accordance with JIS Z0237:2009 at a peeling speed of 300 mm / min and a peeling angle of 180°.

[0275] <Evaluation of writing feel>

[0276] Paper (product name "Campus loose-leaf", model: No-S816B, size: B5, ruled line width: B ruled line, manufactured by KOKUYO Co., Ltd., 20 sheets stacked for use) and ballpoint pen (product name "Orange EG 1.0", oil-based ballpoint pen, pen tip diameter: 1.0 mm, manufactured by BIC Co., Ltd.) were prepared. The evaluator wrote the words "ABCDE" on the paper with the ballpoint pen.

[0277] Next, the protective film was peeled off from the writing feel improving film with a protective film after the peeling test, and the writing feel improving layer was exposed on a glass plate (70 mm long, 150 mm wide, 1.2 mm thick) using a double-sided tape. The words "ABCDE" were written on the surface of the writing feel improving layer using a stylus pen.

[0278] The writing feel (x) of actual writing on paper with a ballpoint pen was compared with the writing feel (y) of writing on the writing feel improvement layer with a stylus pen, and the writing feel was evaluated according to the following criteria.

[0279] (Evaluation Criteria)

[0280] ◎: The writing feel (y) has a vibration and resistance feeling very similar to the writing feel (x), and the writing comfort is good.

[0281] ○: The writing feel (y) is similar to the writing feel (x), the vibration and resistance feel are slightly different, but the writing comfort is good.

[0282] △: The writing feel (y) is different from the writing feel (x) in terms of vibration and resistance, but the writing comfort is within an acceptable range.

[0283] ×: The writing feel (y) is different from the writing feel (x) in terms of vibration and resistance, making it difficult to write and the writing comfort is poor.

[0284] [Table 1]

[0285]

[0286] As shown in Table 1, in the writing feel improving films with protective films of Examples 1 to 15 having a WEM / a value of 0.01 or more and 1.00 or less, the peeling test evaluation was 3 or more, and the occurrence of floating and peeling due to heat was suppressed.

[0287] It was also found that the writing feel was good and the quality of the writing feel improving layer was maintained.

[0288] On the other hand, it was found that in Comparative Examples 1 to 3, the peeling test evaluation was 1 or 2, peeling occurred due to heat, and the quality of the writing feel improving layer was impaired.

[0289] Description of Reference Numerals

[0290] 1…writing feel improving film base material layer

[0291] 2…Writing feel improvement layer

[0292] 3…Adhesive layer

[0293] 4…Protective film substrate layer

[0294] 10…Writing feel improvement film

[0295] 20…Protective film

Claims

1. A writing feel improving film with a protective film, characterized in that: The writing feel improving film with a protective film is a film having a writing feel improving film substrate layer and a writing feel improving layer, and a protective film having an adhesive layer and a protective film substrate layer are laminated in such a manner that the writing feel improving layer of the writing feel improving film contacts the adhesive layer of the protective film. A ratio (WEM / a) of a maximum height of a rounding waviness curve (WEM) of the writing feel improving layer relative to a thickness a (μm) of the adhesive layer is 0.01 or more and 1.00 or less.

2. The writing feel improving film with a protective film according to claim 1, characterized in that: The writing feel improving layer has a maximum height (WEM) of a rounding waviness curve of 0.1 μm or more and 20 μm or less.

3. The writing feel improving film with a protective film according to claim 1 or 2, characterized in that: The thickness a (μm) of the adhesive layer is 5 μm or more and 50 μm or less.

4. The writing feel improving film with a protective film according to claim 1 or 2, wherein: The interlayer peeling force between the writing feel improving film and the protective film is 800 mN / 25 mm or less.

Citation Information

Patent Citations

  • Writing feeling improving film

    CN108070328A

  • Shared blackboard, writing tool and writing induction panel

    CN109407892A

  • Writing feel improving sheet

    US20210089159A1